PELATIHAN PUBLIKASI JURNAL INTERNASIONAL BEREPUTASI BAGI MAHASISWA UIN KH. ABDURRAHMAN WAHID - Abdul Khobir; Ana Chonitsa; Muhammad Maskur Musa; Amma Chorida Fadhila; Teguh Handoyo; Inayah Priyatun; Siti Salamah; Hendri Hermawan Adinugraha (LPPM Universitas Bina Bangsa, 2022)
Training on publication of reputable international journals for students is a training carried out to improve and increase the ability to create and publish journals. With this training, students are more aware of the needs of publishing and producing scientific papers, this is because a lot of information and knowledge are already digital-based. The purpose of holding training on the publication of reputable international journals is that FTIK students are expected to have experience and be able to publish reputable international journals. This service method uses four stages of activities, namely material presentation, journal templating, discussion, and article submission. The results of this service show that this training produces several articles that have been submitted in reputable international journals, including: Journal of Educational Sciences, Journal of Education and Instruction, Journal of Educational and Social Research, Journal of Learning, Teaching, and Educational, Journal of Social Studies Education Research, Journal of Islamic Thought and Civilization, Review of International Geographical Education Online, Turkish Online Journal of Distance Education , Education Reform Journal, Higher Education Governance and Policy , The Journal of Gifted Education and Creativity , The journal of Education &Youth Research (EYOR) , Turkish Online Journal of Distance Education (TOJDE), International Online Journal of Primary Education (IOJPE), Journal of Education and Future – JEF, International e-Journal of Advances in Education (IJAEDU) , Journal of Teacher Education and Educators, Journal of Teacher Education and Lifelong Learning, International Journal of Assessment Tools in Education (IJATE)